Active control of thermal buckling for plates using a temperature feedback control method. (6th March 2019) - Li, Jinqiang; Li, Fengming
Abstract: The active control of thermal buckling for sandwich, laminated, gradient and uniform plates with piezoelectric materials subjected to uniform temperature rise is studied. A temperature feedback control strategy with external control voltage is proposed to control the thermal buckling and the critical buckling temperature is enlarged obviously. The inter-laminar stresses for sandwich and laminated plates by the present temperature feedback control method is compared with those through the constant actuator voltage control method proposed by other researchers, and the advantage of the present method is discussed. The stress distributions of gradient plate are simulated and it is found that the variation law of stress distribution is consistent with the volume fraction distribution of the piezoelectric ceramics. The distribution of piezoelectric components on the active control of thermal buckling is also studied and it is observed from the results that the piezoelectric materials distributed near the surface of plate play more important role than near the center of plate.